2007
DOI: 10.4049/jimmunol.178.10.6297
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of a Productively Rearranged Ig VDJCα Does Not Require the Presence of HS4 in the Igh 3′ Regulatory Region

Abstract: V gene assembly, class switch recombination, and somatic hypermutation are gene-modifying processes essential to the development of an effective Ab response. If inappropriately applied, however, these processes can mediate genetic changes that lead to disease (e.g., lymphoma). A series of control elements within the Ig H chain (Igh) locus has been implicated in regulating these processes as well as in regulating IgH gene transcription. These include the intronic enhancer (Eμ) and several elements at the 3′ end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Finally, the in vitro capacity to secrete various Ig isotypes was unaffected by the knockout. The fact that hs4 was not required for Ig secretion is in agreement with the recent study of Zhang et al (19), who reported, using various bacterial artificial chromosomes and the plasmocytoma cell line 9921, that transcription of a productively rearranged Ig VDJC␣ does not require the presence of hs4 in the 3ЈRR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the in vitro capacity to secrete various Ig isotypes was unaffected by the knockout. The fact that hs4 was not required for Ig secretion is in agreement with the recent study of Zhang et al (19), who reported, using various bacterial artificial chromosomes and the plasmocytoma cell line 9921, that transcription of a productively rearranged Ig VDJC␣ does not require the presence of hs4 in the 3ЈRR.…”
Section: Discussionsupporting
confidence: 91%
“…A predominant role for hs3b in this later study is difficult to support since deletion of the hs3a element (which shares 98% of homology with hs3a) has no effect (12). As previously suggested (12,19), this finding might reflect extensive functional redundancy among these elements (in cooperation or not with other elements in the locus). Deletion of only one of the four 3Ј IgH enhancers can be easily supplanted by the activity of the three remaining enhancers, with deletion of a pair of them becoming more problematic for the cell.…”
Section: Discussionmentioning
confidence: 56%
“…However, a distinct attraction of using an IgH translocus in which the IgH C regions are of endogenous origin is that regions toward the 39 end of the IgH locus are known to play a major role in achieving efficient Ig class switch recombination as well, probably as optimal IgV gene somatic hypermutation (19,51,52). There are substantial differences between mouse/rat and human in the sequences in this enhancer region of the IgH locus, located some 30 kb downstream of Ca (53).…”
Section: Discussionmentioning
confidence: 99%
“…Southern blot analyses were performed as described previously, using ϳ10 -30 g of mouse tail-tip DNA or liver DNA (30).…”
Section: Southern Blot Analysesmentioning
confidence: 99%